ANALISIS PENENTUAN BIAYA PEMBUATAN AKTA JUAL BELI BERDASARKAN ASPEK AKUNTANSI KEPERILAKUAN ( Studi Kasus Pada Kantor Notaris Dan Pejabat Pembuatan Akta Tanah Gervatius Portasius Mude, S.H., M.H) - Fransiska Natalia Desita; Pipiet Niken Aurelia; Wihelmina Maryetha Yulia Jaeng (Jurnal Projemen UNIPA, 2025)
This study aimed to analyze the mechanism of determining the cost of drafting a Sale and Purchase Deed (AJB) based on behavioral accounting aspects at the office of Notary and Land Deed official (PPAT) gervatius Portasius Mude, S.H., M.H in Sikka Regency. The problems raised in this study included how the menchanism of AJB cost determination was carried out and how behavioral accounting aspects were applied in this practice. The study employed a qualitative descriptive approach with a case study method. Data were obtained throught interviews, observation, and documentation, then analiyzed using five behavioral accounting aspecst according to Suartana (2010), namaly : firm theory and managerial behavior, budgeting and planning, decision-making, control, and reporting. The results showed that the determination of AJB costs was not solely based on ATR/BPN regulations of 1%, but also considered the client's socio-economic flexibility. The mechanism of cost determination was conducted orally and through negotiation. Values such as ethics, professionalism, and service became important considerations in decision-making. The findings implied that managerial decisions in AJB cost determination were strongly influenced by individual behavior, leadership characteristics, and socio-contextual considerations.This study aligns with agency theory, which emphasizes the principal-agent relationship between clients and Notary/PPAT, as well as the importance of transparency and control in minimizing conflicts of interest